2019
DOI: 10.18502/fid.v16i2.1362
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of the Essential Oil Obtained from the Seed and Oleo-Gum-Resin of Ferula assa-foetida Against Oral Pathogens

Abstract: Objectives: The objective of this study was to evaluate the antimicrobial activity of the essential oil obtained from oleo-gum-resin and seeds of Ferula assa-foetida. Materials and Methods: Ferula assa-foetida plants were collected from Tabas, Yazd Province, Iran, during summer 2017. Then, essential oils were obtained from its seeds and oleo-gum-resin using hydrodistillation. Gas chromatography-mass spectrometry (GC-MS) test was performed to determine the contents of the essential oils. Four different co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Identification of volatile organic compounds (VOCs) of A. thaumasia and T. cylindrosporum using GC-MS analysis. Ferula assa-foetida oil, having antibacterial activity against Streptococcus mutans, S. sanguis, S. salivarius, S. sobrinus, and Lactobacillus rhamnosus(Daneshkazemi et al, 2019) Salmali Niryasa having antimicrobial activity against Klebsiella pneumoniae, Staphylococcus aureus, E. coli, and Candida albicans(Divya and Prabhu, 2015) It was found in Myrcia ovata oils having antifungal activity against Colletotrichum acutatum, Plenodomus destruens, and Thielaviopsis paradoxa(White et al, 2019) Salmali niryasa having antimicrobial activity against Klebsiella pneumoniae, Staphylococcus aureus, E. coli, and Candida albicans(Divya and Prabhu, 2015) …”
mentioning
confidence: 99%
“…Identification of volatile organic compounds (VOCs) of A. thaumasia and T. cylindrosporum using GC-MS analysis. Ferula assa-foetida oil, having antibacterial activity against Streptococcus mutans, S. sanguis, S. salivarius, S. sobrinus, and Lactobacillus rhamnosus(Daneshkazemi et al, 2019) Salmali Niryasa having antimicrobial activity against Klebsiella pneumoniae, Staphylococcus aureus, E. coli, and Candida albicans(Divya and Prabhu, 2015) It was found in Myrcia ovata oils having antifungal activity against Colletotrichum acutatum, Plenodomus destruens, and Thielaviopsis paradoxa(White et al, 2019) Salmali niryasa having antimicrobial activity against Klebsiella pneumoniae, Staphylococcus aureus, E. coli, and Candida albicans(Divya and Prabhu, 2015) …”
mentioning
confidence: 99%
“…In accordance with the result, a conclusion was made that the essential oil of the Pathani F. assa-foetida variety exhibited a good antibacterial activity (Escherichia coli and Bacillus subtilis); whereas, the essential oil of Irani the F. assa-foetida variety exhibited good fungicidal activity (Penicillium chrysogenum and Aspergillus ochraceus). Furthermore, a study revealed the antimicrobial properties of the essential oil of the resin and seed of F. assa-foetida against various oral bacteria such as Lactobacillus rhamnosus, Streptococcus salivarius, Streptococcus sanguis, Streptococcus sobrinus, and Streptococcus mutans (Daneshkazemi et al, 2019). The resulting analysis displayed that the oleogum-resin essential oil had significant and effective antibacterial activities as compared to the seed essential oil (p < 0.001).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The resulting analysis displayed that the oleogum-resin essential oil had significant and effective antibacterial activities as compared to the seed essential oil (p < 0.001). Jahani et al, (2015) reported the antibacterial activity of gelatin nano-capsules formulated from the essential oil of F. assa-foetida. Mallahi et al, (2018) studied the potential of Ferula essential oil to increase the shelf-life of Gerbera jamesonii (Gerbera Daisy) flower by inhibiting the pathogenic bacteria.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The volatile oils of the Pathani variety were effective antibacterial, whereas Irani varieties act as antifungal agents (Divya et al, 2014). The essential oils obtained from seed and oleo gum resin of F. asafoetida showed antimicrobial effects against oral pathogens (Alireza et al, 2019). It also induced hyperglycemia (Al-Awadi, 1985) and was highly effective in the treatment of Alzheimer disease (Shereen et al, 2013).…”
Section: Origin and Distributionmentioning
confidence: 99%